Protection Of Human Rights In The Context Of Indonesian Constitutional Law Against The Functions Of State Institutions - Manullang, Elika; Sinaga, Budiman N.P.D; Siburian, Kasman (Indonesian Journal Publisher, 2025)
In light of the Indonesian Constitution, this paper examines the function of the National Human Rights Commission of Indonesia (Komnas HAM). As an impartial organization that looks into, keeps an eye on, and mediates human rights abuses, the Komnas HAM plays a crucial role. However, the Komnas HAM's existence is beset by a number of challenges, such as a lack of political and financial backing, overlapping powers with other state bodies, and restricted enforcement power. The relationship between the Indonesian Court of Human Rights and Komnas HAM is another significant matter. For significant human rights abuses to be successfully prosecuted, these two agencies ought to cooperate. In order to boost human rights protection in Indonesia, this study highlights the necessity of better interagency collaboration, strengthened legal frameworks, and increased political commitment. Thus, this study improves Indonesia's human rights protection and contributes significantly to our understanding of the Komnas HAM's position within the framework of the Indonesian Constitution.